Pengembangan LKPD Matematika dengan Pendekatan Kontekstual Siswa Kelas V SDN 88 Bengkulu Tengah - Cici Lestisia; Agus Susanta; Irwan Koto (Universitas Bengkulu, 2023)
This study aims to 1) Describe the Development of Mathematics LKPD based on the contextual approach of fifth grade students 2) Describe the Feasibility of LKPD Mathematics based on the contextual approach of fifth grade students. 3) Describe the withdrawal of LKPD Mathematics based on the contextual approach of fifth grade students of SD Negeri 88 Bengkulu Tengah. This type of research is Research and Development (R&D) research. The population in this study were all grade V SDN 88 Bengkulu Tengah accredited A. The sample in this study was 15 students. The assessment instruments in this study used a questionnaire of the validation of LKPD experts and practitioners obtained from the calculation of Aiken's V. index The attractiveness questionnaire was obtained from students' responses to LKPD obtained from the Likert Scale. Data obtained from the results of the validation of the feasibility of LKPD on the Content / Material aspects 0.7144, Language aspects 0.7, Design / graphic aspects 0.714, the average agreement of experts and practitioners on the feasibility of LKPD obtained 0.709. Analysis of student responses obtained a maximum score of 65.333 with interesting criteria. Thus it can be concluded that Contextual Based Mathematics LKPD is worth testing in a limited scale.